2018
DOI: 10.1017/s0950268818002716
|View full text |Cite
|
Sign up to set email alerts
|

New product, old problem(s): multistate outbreak of Salmonella Paratyphi B variant L(+) tartrate(+) infections linked to raw sprouted nut butters, October 2015

Abstract: Summary A cluster of Salmonella Paratyphi B Variant L(+) Tartrate(+) infections with indistinguishable pulsed-field gel electrophoresis patterns was detected in October, 2015. Interviews initially identified nut butters, kale, kombucha, chia seeds, and nutrition bars as common exposures. Epidemiologic, environmental, and traceback investigations were conducted. Thirteen ill people infected with the outbreak strain were identified in 10 states with illness onset during July 18–November 22, 2015. Eight of 10 (80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Investigators can conduct open-ended interviews to ask questions about exposure to other foods and animals, although these are time-consuming for both interviewers and patients. However, open-ended interviews and other approaches (e.g., examination of shopper card records) have been used with success to identify new outbreak sources and solve outbreaks ( 11 , 15 , 16 ). Finally, a suspected outbreak source was identified in 28% of multistate investigations in 2016; however, sources were not confirmed because of insufficient traceback or laboratory data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators can conduct open-ended interviews to ask questions about exposure to other foods and animals, although these are time-consuming for both interviewers and patients. However, open-ended interviews and other approaches (e.g., examination of shopper card records) have been used with success to identify new outbreak sources and solve outbreaks ( 11 , 15 , 16 ). Finally, a suspected outbreak source was identified in 28% of multistate investigations in 2016; however, sources were not confirmed because of insufficient traceback or laboratory data.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic data included 1) a higher than expected proportion of patients with exposure to the same food or animal before illness onset and 2) two or more unrelated patients who ate at the same restaurant, shopped at the same grocery store, or attended the same event. To determine whether a higher than expected proportion of patients was exposed to a particular food or animal, investigators frequently used techniques such as a binomial model to compare the proportion of patients associated with an outbreak with healthy persons who participated in the FoodNet Population Survey ( 10 , 11 ). Traceback data included shipping, purchase, or other information that suggested a common point of contamination in the distribution chain of food products or animals ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Processors relying on refrigeration must take care to confirm that refrigeration conditions are < 4°C and/or limit the soaking time at lower temperatures to prevent Salmonella growth. Investigations surrounding the 2015 Salmonella Paratyphi B outbreak linked to "sprouted" nut butters reported that the company conducted their soaking process under refrigeration but they did not apply a validated kill step (12). This situation demonstrates that refrigerated soaking may be an important control to prevent the growth of Salmonella; however, this approach was insufficient to eliminate risk associated with contaminated starting ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Three outbreaks have been linked to the consumption of "sprouted" products, specifically sprouted chia seed powder, cashew nut cheese, and raw sprouted nut butters (11,12,19). In response to the chia powder outbreak, Health Canada and the Canadian Food Inspection Agency conducted an investigation to determine the level of Salmonella contamination in the implicated product (sprouted chia powder) and a co-manufactured product (sprouted flax powder).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, 17 were identified as the Java biotype, while 10 belonged to the sensu stricto type. Multilocus sequence typing (MLST) analysis revealed four different sequence types (ST) within these strains: ST42 (11), ST86 (10), ST2814 (5), and ST135 (1). ST42, ST2814, and ST135 corresponded to the Java biotype, while ST86 represented sensu stricto.…”
Section: Salmonella Paratyphi B Isolates In Jiangsumentioning
confidence: 99%